Vertical Structure and Surface Impact of Atmospheric Rivers Reaching Antarctic Sea Ice and Land - Cordero-Carrasco, R (ELSEVIER SCIENCE INC, 2025)
Recent extremes in Antarctic temperature, surface melt and sea ice loss have been robustly linked to the occurrence of atmospheric rivers (ARs). However, the precise mechanisms that generate variations in the surface impacts of ARs are poorly understood, especially in the Antarctic. Based on Arctic evidence that the vertical and horizontal advancement of ARs over sea ice strongly depends on meteorological conditions, the season, as well as the underlying surface before reaching sea ice, we investigate the vertical structure and impact of extreme ARs reaching sea ice and also the Antarctic ice sheet. Based on MERRA-2, ERA5 and six CMIP6 models (1985-2014), we find that surface inversions are twice as likely to occur during AR conditions in austral summer compared to climatology, and also find a significant increase in the frequency of double inversions. Our results suggest that land-locked sea ice acts as a protective barrier for the Antarctic continent, diminishing wind speeds and moisture levels, and that seasonal variations exhibit a predominant influence of downward shortwave and longwave flux anomalies in summer and winter, respectively. Furthermore, surface warming induced by ARs over sea ice is notably enhanced under conditions of upper-air subsidence, coupled with reduced cloud cover and precipitation in summer, and intensified turbulent heat and downward longwave fluxes in winter. By contrast, the surface warming associated with ARs reaching land is mainly caused by the cloud radiative effect, where the most intense ARs are further enhanced by positive downward sensible and latent heat fluxes.